2021
DOI: 10.1021/jacs.1c05032
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Coordination Environment of Single-Atom Catalysts and Their Proximity to Photosensitive Units for Boosting MOF Photocatalysis

Abstract: Well-organized photosensitive units and catalytic sites in proximity are crucial for improving charge separation efficiency and boosting photocatalysis. Herein, a general and facile strategy for the construction of high-loading (>4 wt %) single-atom catalysts (SACs) with a tunable coordination microenvironment has been developed on the basis of metal–organic frameworks (MOFs). The neighboring −O/OH x groups from a Zr6-oxo cluster in the MOFs provide lone-pair electrons and charge balance to immobilize the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
189
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(192 citation statements)
references
References 60 publications
3
189
0
Order By: Relevance
“…According to different interactions, they are divided into different types of catalysts, mainly including metal single atoms anchored on the surface of metal oxides, metals, carbon-based materials, metal-organic framework materials (MOFs), covalent organic framework (COF) materials, and composite materials. The construction of a single-atom catalyst with a controllable coordination environment and close to the photoactive site in the MOF material can effectively promote the charge transfer during the photocatalytic reaction and enhance the photocatalytic performance [11][12][13][14][15][16][17].…”
Section: Structure and Activity Of A Single-atom Catalystmentioning
confidence: 99%
“…According to different interactions, they are divided into different types of catalysts, mainly including metal single atoms anchored on the surface of metal oxides, metals, carbon-based materials, metal-organic framework materials (MOFs), covalent organic framework (COF) materials, and composite materials. The construction of a single-atom catalyst with a controllable coordination environment and close to the photoactive site in the MOF material can effectively promote the charge transfer during the photocatalytic reaction and enhance the photocatalytic performance [11][12][13][14][15][16][17].…”
Section: Structure and Activity Of A Single-atom Catalystmentioning
confidence: 99%
“…Defect engineering, which can generate missing-linker defects in the MOF structure by using modulators, has the potential to solve these two problems with UiO-66-NH 2 . Previous computational and experimental studies have demonstrated that the introduction of missing-linker defects in UiO-66-NH 2 is an effective approach to enhance photocatalytic activity in hydrogen production and CO 2 reduction. In the photoexcitation of UiO-66-NH 2 , an energy is required to transfer electrons from the excited 2-aminoterephthalate linkers to the unoccupied d orbitals of the zirconium–oxo clusters (Δ E LCCT ) as well as to excite the linkers (Δ E Abs ). ,, By introducing missing-linker defects into the UiO-66-NH 2 structure, we can decrease the value of Δ E LCCT by lowering the level of the unoccupied d orbitals of zirconium . On the other hand, it is widely known that hydrophobic catalysts are effective in suppressing H 2 O 2 decomposition due to rapid separation of H 2 O 2 and catalyst particles. , Acetic acid, which is an agent for creating missing-linker defects, is spontaneously coordinated to missing-linker defects on zirconium–oxo clusters during the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, these reactive sites consist of metal atoms that are undercoordinated and, thus, can either exhibit catalytic properties themselves or can be further modified via a variety of synthetic transformations to support other metal-based species or organic ligand(s). , In the context of photocatalysis, the well-defined distances between light-sensing chromophores and catalytic sites are highly conducive toward precise characterization of the photoinduced charge and energy transfer in MOFs. Among some common approaches in the field are porphyrin-based linkers, which can support a single metal atom and allow reactants to approach axially, encapsulation of noble metal single atoms, , and precise defect engineering, which allows for positioning of the catalytic sites in an optimal fashion; zirconium-based MOFs are particularly attractive for this approach as a result of the rich variety of linker coordination motifs and potential catalyst grafting sites available to the Zr 6 O 4 (μ 3 -OH) 4 -derived node. , …”
Section: Introductionmentioning
confidence: 99%